The Establishment of Religious Landscapes and Local Social Life in Nanshan and Beishan, Dazu District, in the Song Dynasty - Jie Zhou (Religions)
As an exemplary and quintessential representation of China’s late-stage religious stone-carving art, previous research on the Dazu Rock Carvings has primarily concentrated on the typical cave remains in core areas like Baoding and Beishan. These investigations have been highly adept at archeological typology and iconographic analysis. This study, based on 134 extant inscriptions, reassesses the Beishan and Nanshan stone-carving complexes from the perspective of cultural heritage integrity. Through long-term landscape analysis, we uncovered their distinctive value in the construction of religious spaces during the Northern and Southern Song Dynasties. During the Song Dynasty (Zhao Song Dynasty), Buddhism held sway in Beishan, while Nanshan developed a comprehensive Taoist pantheon system encompassing the Three Pure Ones (Sanqing) and the Six Imperial Divinities (Liuyu). Together, they formed a religious spatial pattern of “Sakyamuni in Beishan and Taoist deities in Nanshan”. Furthermore, since the Shaoxing era (1131–1162), inscriptions left by Confucian scholars and officials during their visits to these two mountains have been frequently encountered. This spatial overlap phenomenon mirrors the profound integration of religious practices and secular power in the Bashu region during the Song Dynasty. This research breaks through the traditional case-study paradigm. By systematically examining the spatio-temporal evolution of the stone-carving complexes and the network of inscriptions, it reveals that the religious landscape of Dazu is, in essence, the outcome of the cumulative layering of political power, economic resources, and cultural aspirations across diverse historical periods. In particular, the transformation of Beishan and Nanshan from the merit caves of military generals in the late Tang Dynasty to the cultural spaces of the gentry class in the Song Dynasty vividly demonstrates the local practice model in the secularization process of Chinese religious art from the 10th to the 13th century.